Reasons Why People Change Their Alcohol Consumption in Later Life: Findings from the Whitehall II Cohort Study - Britton, Annie (PLoS One, 2015)
PURPOSE: Harmful alcohol consumption among the ageing population is an important public health issue. Very few studies ask drinkers why they change their consumption in later life. The aim of this paper was to determine whether a group of people aged over 60 years increased or decreased their alcohol consumption over the past decade and to determine the reasons for their change. We also examined whether the responses varied by age, sex and socio-economic position (SEP). SUBJECTS AND METHODS: Data were taken from 6,011 participants (4,310 men, 1,701 women, age range 61 to 85 years) who completed questionnaires at phase 11 (2012-2013) of the Whitehall II Cohort Study. RESULTS: Over half the study members reported a change in alcohol consumption over the past decade (40% decreased, 11% increased). The most common reasons given for decreases were as a health precaution and fewer social occasions. Common reasons for increases were more social occasions and fewer responsibilities. The lowest SEP group was less likely to increase consumption compared to high SEP (RR 0.57, 95% CI 0.40 to 0.81). Women were more likely to increase consumption in response to stress/depression than men (RR1.53, 95% CI 1.04 to 2.25). Compared to high SEP, the lowest SEP group was less likely to reduce as a health precaution (RR 0.61, 95% CI 0.38 to 0.76). CONCLUSIONS: Alcohol consumption in late life is not fixed. Reasons for change vary by age, sex and SEP. Such information could be used to tailor intervention strategies to reduce harmful consumption.